Comparison of peak expiratory flow rate (PEFR) before and after physical exercise in obese and non-obese children - Febrina Z. Siregar; Gabriel Panggabean; Ridwan M. Daulay; Helmi M. Lubis (Paediatrica Indonesiana, 2009)
Background  Obesity  has  been  associated  with  respiratorycomplications  and  it  is  believed to reduce lung volume. Obesityimposes additional stress on  ventilation  during exercise  andmay even result in pulmonary function impairment. Exerciseinduced-bronchospasm has also been found in obese children.Lung function tests  can  be useful to confirm diagnosis, responseto therapy, or prediction of lung and respiratory diseases.  Thepeak  flow  meter  is  an  inexpensive, practical  way  to measure lungfunction, and  can  detect the early warning signs  of  a decrease inlung function.Objective  To  compare the peak expiratory  flow  rate (PEFR) beforeand after physical exercise in obese and non-obese primary schoolboys aged 6 to  12  years old.Methods  A quasi-experimental study using the one group pretest-posttest design was performed  on  30  obese children  (BMI  abovethe  95<h  percentile)  and  30 non-obese children  (BMI  betweenthe  5<h  - 85'h percentile) using a mini-Wright peak  flow  meterto evaluate the PEFR before  and  after eight minutes  of  physicalexercise. Height, weight, body mass index,  and  physical statuswere determined before testing.Results  The  PEFR before  and  after exercise were 14.80 for obesechildren and 9.76 for non-obese children.  The  mean value forPEFR between obese and non-obese children was significantlydifferent  (P<0.05).Conclusion  The  PEFR for obese children  is  significantly lowerthan  non  obese children  even  before physical exercise.